ANALISIS PRODUKSI DAN EKONOMI PETERNAKAN AYAM BROILER SISTEM KANDANG CLOSED HOUSE POLA KEMITRAAN (Studi Kasus Peternakan Plasma PT. Cemerlang Unggas Lestari Kabupaten Kebumen) - Irfandi Nuary; Novie Andri Setianto; Bambang Hartoyo (ANGON: Journal of Animal Science and Technology, 2022)
Background. The efforts of chicken broiler farmers to know their business productivity through farm management evaluations is one of these in terms of economic analysis and production. A closed house system farm needs high capital value. For that reason, it needs a partnership system for develop the farm business itself. This research aims to determine the productivity of plasma farms with closed house systems at PT. Cemerlang Unggas Lestari Kebumen Regency by conducting an analysis in terms of economy and production. Materials and Methods. The research was conducted by comparing the productivity of PT. Cemerlang Unggas Lestari plasma farms, Ario Bhirowo’s farm and Mitra Sejahtera II’s farms using an economic analysis such as total production costs, revenue, income, BEP price and BEP product, R/C ratio, Payback Period (PP) and Performance Index (IP) for production analysis. Results. The results showed that Ario Bhirowo’s farm with a population of 28.500 had a total production cost of Rp 935.061.829,00 per period, revenue and income Rp 1.005.589.158,00 and Rp 70.527.329,00 per period, BEP price of Rp 16.725,00/Kg and BEP product 52,298 Kg, R/C ratio 1,0754 and PP 36,9 period. Meanwhile the Mitra Sejahtera II farm with a population of 62.800 had a total production cost of Rp 2.001.845.495,00 per period, total revenue and income of Rp 2.204.352.482,00 and Rp 202.506.987,00 per period, BEP price Rp 16.311,00/Kg dan BEP product 113.174 Kg, R/C ratio 1,1012 and PP 22,7 period. Conslusion. In terms of production analysis, the two farms showed that IP value were not much different. The IP value for Ario Bhirowo’s farm was 368 and Mitra Sejahtera II’s was 369.